(untitled) (Agricultural Engineering, 2017)
The paper analyses technical equipment of the selected dairy farms. Data from questionnaires carried out in 96 farms in 2015 constituted a research material. Municipalities Lszewo-Borki in Mazowieckie Voivodeship were covered by the survey. A survey questionnaire, which consisted of two parts, was a research instrument. The first concerned general information on a farm and its owner, and the other consisted of eight questions on technical equipment used for breeding dairy cows. The research allowed to determine that farmers assessed the condition of their machinery park as average (50%) or good (40%). One out of ten farmers claimed that the used machinery park in a farm is in a bad condition. Majority of respondents have allotted from PLN 20 to 50 thousand for investments related to enhancement of a machinery park within the last 5 years. On the other hand, a considerable part of farms allotted up to PLN 20 thousand for development of a machinery park. The investigated group included also farms, which allotted more than PLN 500 thousand for development of a park.